The Effect of Gadget Intensity and Parental Supervision on Child Discipline at Asya'rif Hidayat Kindergarten - Andriyani, Andriyani; Kurniasari, Kurniasari; Supriyadi, Supriyadi; Syarifah, Dewi Syarifah (IJBLE Scientific Publications Community Inc., 2025)
This research investigates the influence of device usage intensity and parental supervision on child discipline. A quantitative approach was used, with data collected from 30 respondents. Descriptive statistical analysis and inferential statistics, including Pearson correlation and multiple linear regression analysis, were employed to analyze the data. The results revealed that both device usage intensity and parental supervision have significant positive effects on child discipline. The regression analysis indicated that parental supervision had a stronger influence on child discipline than device usage intensity. Furthermore, the ANOVA test confirmed the overall significance of the regression model. Correlation analysis showed a moderate positive relationship between child discipline and device usage intensity, while a stronger relationship was found between child discipline and parental supervision. The study concludes that parental supervision is a more influential factor in improving child discipline than device usage intensity, highlighting the importance of parental involvement in managing children's digital device usage.